Prosecutor’s Office of Russia: Analysis of Legal Sources (1722–2015) - PAVLOV, Valeriy S. (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article analyzes and systematizes legal acts that significantly influenced the creation and development of the Prosecutor’s Office of Russia since its creation by Peter the Great in 1722 up to 2015 inclusively. The material is given in accordance with the periodization proposed by the author: (1) Tsarist Russia period (January 12, 1722 — February 27, 1917); (2) period of the bourgeois-democratic Russian Republic (February 27, 1917 — October 25, 1917); (3) Soviet period (1922–1991), and (4) The Russian Federation period (1922–2015). Main sources of study are Complete Collection of the Laws of the Russian Empire (1649–1913), Collection of Legislative Enactments and Directives of the Tsar’s Government (1914–1917), Bulletin of the Russian Provisional Government (1917), Collection of Legislative Enactments of the RSFSR (1917–1938), The Bulletin of The Supreme Soviet of the Soviet Union (1941–1984), the Bulletin of the Congress of People’s Deputies of the Russian SFSR and The Supreme Soviet of the Soviet Union (1990–1992), Collection of the Russian Federation Legislation (1992–2015).